Températures et indices bioclimatiques dans le vignoble du Val de Loire dans un contexte de changement climatique - Cyril Bonnefoy; Hervé Quenol; Olivier Planchon; Gérard Barbeau (EchoGéo)
Spatial and temporal climate variability at regional scale can sometimes be important. Spatial observed differences can be explained by the nearness or not of ocean, topography, elevation or latitude… Important climatic nuances are observed in the Loire Valley, one of the big French wine-producing areas, because of its East-West orientation. The oceanic influences close to the coast are gradually deteriorated to the East with more continental influences. As a result various climatic characteristics are observed in the Loire Valley vineyards. Since the middle of the 20th century, a regional warming has been noticed. This warming has been more significant since the end of the 80’s. This increase of temperature is reflected in the bioclimatic indices.